2012
DOI: 10.3367/ufnr.0182.201205c.0521
|View full text |Cite
|
Sign up to set email alerts
|

Fe - C and Fe - H systems at pressures of the Earth's inner core

Abstract: The solid inner core of the Earth is predominantly composed of iron alloyed with several percent Ni and some lighter elements, Si, S, O, H, and C being the prime candidates. To establish the chemical composition of the inner core it is necessary to find the range of compositions that can explain its observed characteristics. Recently, there have been a growing number of papers investigating C and H as possible light elements in the core, but the results are contradictory. Here, using ab initio simulations, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…• The stability of Fe 3 C is evaluated under dynamic compression, and no density discontinuity is observed up to 245 GPa • Thermal equation of state of Fe 3 C is established by combining dynamic and static compression data • The density of Fe 3 C is 5% lower than that of the inner core, and Fe 3 C is unlikely a component of the inner core predictions (Bazhanova et al, 2012;Weerasinghe et al, 2011) revealed that Fe 7 C 3 might decompose into more stable stoichiometries such as Fe 3 C and Fe 2 C at the inner core pressures. There is currently no consensus concerning the stable iron carbide liquidus phase of the Fe-C system at the ICB.…”
Section: 1029/2019gl084545mentioning
confidence: 99%
“…• The stability of Fe 3 C is evaluated under dynamic compression, and no density discontinuity is observed up to 245 GPa • Thermal equation of state of Fe 3 C is established by combining dynamic and static compression data • The density of Fe 3 C is 5% lower than that of the inner core, and Fe 3 C is unlikely a component of the inner core predictions (Bazhanova et al, 2012;Weerasinghe et al, 2011) revealed that Fe 7 C 3 might decompose into more stable stoichiometries such as Fe 3 C and Fe 2 C at the inner core pressures. There is currently no consensus concerning the stable iron carbide liquidus phase of the Fe-C system at the ICB.…”
Section: 1029/2019gl084545mentioning
confidence: 99%
“…Carbon has been commonly considered as a potential major light element as it is the fourth most abundant element in the solar system and its abundance reaches 3.2 wt % in the carbonaceous chondrites-Ivuna (CI). A number of iron carbide phases (e.g., Fe-rich Fe-C alloys, Fe 3 C, Fe 7 C 3 , or Fe 2 C) have been proposed to be the carbon-bearing host phase in the core [e.g., Wood, 1993;Dasgupta et al, 2009;Lord et al, 2009;Nakajima et al, 2009;Tateno et al, 2010;Bazhanova et al, 2012;Fei and Brosh, 2014;Liu et al, 2016a]. Studies of their high-pressure-temperature (P-T) properties including crystal structures and melting curves are thus essential to understanding Earth's accretion and early differentiation as well as the deep-carbon cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of iron hydride FeH under pressure has been achieved several decades ago [24] and in recent years polyhydrides FeH 3 [25] (above 86 GPa) and FeH 5 [26] (above 120 GPa) have been reported. Early DFT calculations focused on known simple structure types [27] but CSP has since contributed meaningfully in exploring the binary Fe-H phase diagram [28][29][30][31] , both motivating and confirming the recent experimental efforts.…”
Section: Volatiles In Iron-rich Coresmentioning
confidence: 83%
“…Fe-C. Two relatively simple iron carbides are known and have been subjected to detailed experimental and DFT investigations: Fe 3 C, an iron-rich compound important in metallurgy [33] , and Fe 7 C 3 , which forms at relatively low pressures [34,35] . Searching beyond these known compounds, CSP has been used by two groups to find other candidates for high-pressure Fe-C compounds [28,36] . Both reported a new phase, Fe 2 C, to become stable at inner core pressure conditions, which has not been seen in experiments so far.…”
Section: Volatiles In Iron-rich Coresmentioning
confidence: 99%
See 1 more Smart Citation